Effect of composite conjugated materials on tissue healing during exercise rehabilitation training - Li, Jie; Zhang, Jing (Frontiers in Chemistry, 2023)
The application of traditional materials to tissue healing in sports rehabilitation training has problems such as poor effect, high rejection reaction, and slow healing speed. It also brings many challenges to the development of sports rehabilitation training. This article aims to explore the impact of composite conjugated materials on tissue healing to promote rapid and efficient tissue healing and improve the effect of sports rehabilitation training. Through research and analysis, this article found that composite conjugated materials have unique biocompatibility and can promote cell growth and differentiation. In skin tissue healing, composite conjugated materials can control the release rate and duration of drugs to promote skin healing. During the fracture healing process, conjugated materials can provide growth factors and extracellular matrix components, stimulate bone cell proliferation and differentiation, and promote fracture healing. In terms of soft tissue injuries, composite conjugated materials serve as supporting structures or matrices, providing a favorable environment for the regeneration of damaged tissue. In the regulation of inflammatory responses, composite conjugated materials reduce inflammatory responses and accelerate the healing process by modulating immune responses. The results of this study show that 1 week after the experiment, the skin healing rates of the control group and the experimental group were 42.55% and 58.17% respectively; 5 weeks after the experiment, the skin healing rates of the control group and the experimental group were 51.28% and 73.24% respectively. After 1, 2, 3, 4, and 5 weeks of experiment, it was found that the average tissue repair rates of the control group were 44.03%, 54.18%, 58.40%, 67.08%, and 72.09% respectively, and the average tissue repair rates of the experimental group were 52.18%, 61.91%, 63.40%, 74.61%, and 85.05% respectively. This study highlights the huge potential of composite conjugated materials in promoting tissue healing and tissue repair, and is of great significance for promoting technological progress in the field of sports rehabilitation and improving rehabilitation effects.